The clinical impact of serum 1,5-anhydro-D-glucitol levels on coronary artery calcification and adverse outcomes assessed by coronary optical coherence tomography in diabetic patients - Teng, Hsin-I; Chen, Hsiang-Yao; Tsai, Chuan-Tsai; Huang, Wei-Chieh; Chen, Ying-Ying; Hsueh, Chien-Hung; Hau, William K.; Lu, Tse-Min (Frontiers in Cardiovascular Medicine, 2022)
Background Serum 1,5-anhydro-D-glucitol (1,5-AG) is a novel biomarker for short-term glycemic status and postprandial hyperglycemia. The association between serum 1,5-AG levels and coronary artery calcification (CAC) through a quantitative assessment using optical coherence tomography (OCT) is unclear. We aimed to evaluate this association using OCT in patients with diabetes mellitus. Methods From June 2016 to December 2019, we prospectively enrolled 256 patients who underwent OCT-guided percutaneous coronary intervention. Half of the patients had diabetes. Patients were followed up for a mean period of 1.8±0.8 years (median: 2.2 years). The relative calcium index and relative lipid core index measured by quantitative OCT analysis were used to evaluate the intra-plaque calcium and lipid levels of culprit plaques. We also analyzed the correlation between serum 1,5-AG levels and long-term major adverse cardiovascular events. Results Serum 1,5-AG levels were significantly lower in diabetic patients than in non-diabetic patients (DM vs. non-DM: 55.6 ± 27.9 µg/mL vs. 63.7 ± 26.1 µg/mL, p=0.016), and lower in fibrocalcified lesions than in fibrotic or fibrolipidic lesions (fibrocalcified vs. fibrotic or fibrolipidic: 42.8 ± 19.1 vs. 72.9 ± 25.2 or 66.4 ± 27.5 µg/mL, p<0.001, respectively). In addition, we found a significant inverse correlation between serum 1,5-AG levels and relative calcium index (r= -0.729, p<0.001). In multivariate Cox regression analysis, low serum 1,5-AG level was identified as an independent predictor for major adverse cardiovascular events in diabetic patients (p=0.044), but not in non-diabetic patients (p=0.751) after adjusting for age and sex. Conclusions This study revealed that low serum 1,5-AG levels were associated with an increased risk of CAC as assessed by OCT, especially in diabetic patients. Low serum 1,5-AG levels may predict future major adverse cardiovascular events in diabetic patients undergoing OCT-guided percutaneous coronary intervention.